Interferon-? and IL-5 production correlate directly in HIV patients Co-infected with mycobacterium tuberculosis with or without immune restoration disease - Oliver, B.; Elliott, J.; Saphonn, V.; Vun, M.; French, M.; Price, Patricia (Mary Ann Liebert, Inc., 2010)
IL-5 and interferon-? responses were investigated in mitogen-stimulated whole-blood cultures from HIV patients with and without Mycobacterium tuberculosis disease, to determine whether an imbalance of Th1/Th2 cytokines contributes to susceptibility to M. tuberculosis disease or to immune restoration disease (IRD) associated with M. tuberculosis after starting antiretroviral therapy (ART). Interferon-? levels were constant on ART, whilst IL-5 levels generally rose over time. We suggest that increased IL-5 production reflects a recovery of CD4 + T cell function and that a Th1/Th2 imbalance is not associated with increased susceptibility to M. tuberculosis disease or IRD associated with M. tuberculosis upon starting ART. Copyright © 2010, Mary Ann Liebert, Inc.